Language and Problems of Knowledge - Rosli Omar (Journal of Modern Languages)
This study considers the probable problems in using computers in language learning, e.g. speaking. The results of the research show that using computers do not reveal real problems on their bands, so to speak, in trying to understand language. It is because of the nature of language, which is such a natural thing that human beings do not attribute any intelligence to it.